A Quick Test of Cognitive Speed (AQT): Usefulness in dementia evaluations in primary care. (March 2013) - Kvitting, Anna S.; Wimo, Anders; Johansson, Maria M.; Marcusson, Jan
Abstract Objective. To validate A Quick Test of Cognitive Speed (AQT) as an instrument in diagnostic dementia evaluations against final clinical diagnosis and compare AQT with the Mini-Mental State Examination (MMSE) and Clock Drawing Test (CDT) in primary care. Design. Primary health care cohort survey. Setting. Four primary health care centres and a geriatric memory clinic in Sweden. Patients. 81 patients (age 65 and above) were included: 52 with cognitive symptoms and 29 presumed cognitively healthy. None of the patients had a previous documented dementia diagnosis. All patients performed MMSE, CDT, and AQT at the primary health care clinic and were referred for extensive neuropsychological testing at a memory clinic. AQT was validated against final clinical diagnosis determined by a geriatric specialist and a neuropsychologist. Main outcome measures. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), likelihood ratios, correlation data, and receiver operating characteristic (ROC). Results. For MMSE, sensitivity and specificity was 0.587 and 0.909; CDT 0.261 and 0.879; and AQT 0.783 and 0.667, respectively. For the combination of MMSE and CDT, sensitivity and specificity was 0.696 and 0.788, for MMSE and AQT 0.913 and 0.636. The ROC curve for AQT showed an area under curve (AUC) of 0.773. Conclusion. Our results suggest AQT is a usable test for dementia assessments in primary care. Sensitivity for AQT is superior to CDT, equivalent to MMSE, and comparable to the combination MMSE and CDT. MMSE in combination with AQT improves sensitivity. Because AQT is user-friendly and quickly administered, it could be applicable for primary care settings.